Rethinking College Student Development Theory Using Critical Frameworks. Issue 3 (1st August 2020) - Andersen, Kent
Abstract: Abes, Jones, and Stewart's Rethinking College Student Development Theory Using Critical Frameworks (2019) is an engaging collection focused on third-wave student development theories. Using critical and post-structuralist theories to reimagine key concepts and practices in student affairs, the collection offers an opportunity for all educators to reexamine key principles of practice as well as the meaning and aims of student development. While the collection may have its limitations, careful examination of the narratives and critical discussions will broaden the worldview of those educators who take the time to read it.